Volume 3: 16th International Conference on Advanced Vehicle Technologies; 11th International Conference on Design Education; 7t 2014
DOI: 10.1115/detc2014-35023
|View full text |Cite
|
Sign up to set email alerts
|

Requirements Evolution: Relating Functional and Non-Functional Requirement Change on Student Project Success

Abstract: This paper presents findings from a study of the evolution of requirements in eight parallel student semester long design projects. Weekly requirements documents were collected and analyzed for the number of functional and non-functional requirements defined by each team. Trends were compared with end of project performance success. The findings provide suggestive, not definitive, evidence that (a) a higher number of defined requirements predicted higher project success, (b) early functional requirement defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…Even though the teams with the most design requirements in both years performed well, other teams in the top tier did not necessarily have more requirements than the bottom tier teams. This is not consistent with a previous study which found requirement quantity to be positively correlated with design outcomes in student projects [6]. However there was limited variation in requirement quantity among teams (except the two teams with the most requirements), the conclusion here is not strong.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Even though the teams with the most design requirements in both years performed well, other teams in the top tier did not necessarily have more requirements than the bottom tier teams. This is not consistent with a previous study which found requirement quantity to be positively correlated with design outcomes in student projects [6]. However there was limited variation in requirement quantity among teams (except the two teams with the most requirements), the conclusion here is not strong.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies conducted with student designers suggested that it is important to continue capturing design requirements throughout the project. Those who had a higher number of final requirements were more likely to be successful because they were more likely to gain deeper understanding of the design problem at the end of the project [6]. In addition, it was found that writing good design requirements that are complete and detailed is key to the success of student design teams [8].…”
Section: Design Requirements Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] The preceding course in which students are taught the structured design process, tools, and methods through case study, discussion, and application in a controlled project has also be used as an investigated playground to understand student performance on design. [17][18][19] This aligns with work by others in which capstone design teams are used as experimental subjects in the field of design research. [20][21][22][23] The case study of this research is used to investigate the evolution of requirements in the requirements document of novice designers was conducted on one of the capstone design projects from spring 2011.…”
Section: Design Project and Participantsmentioning
confidence: 73%
“…It also allows course instructors to gauge student progress on their product design and development process. This has been noted by a number of other experiential course instructors [1], [5], [8], [12].…”
Section: Product Design and Development Coursementioning
confidence: 99%